The Influence of Work Flexibility on Employee Performance in The Kutambaru District Office - Irwansyah, Irwansyah; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of work flexibility on employee performance in Kutambaru District Office Employees. This research was carried out at the Kutambaru District Office. The type of research is associative quantitative. The sample in this study was 15 employees of the Kutambaru District Office. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 15 people. The research results show that work flexibility has a significant influence on employee performance as shown by the T-Statistic value of 2.361 > 1.753 and the P value of 0.000 < 0.05. This shows that improvements in Work Flexibility can improve the Performance of Kutambaru District Office Employees Kutambaru District Office.